Validation of the Contextual Sensation-Seeking Questionnaire for skiing and snowboarding among Chinese adult skiers and its relationship with risk-taking behavior - Guo, Zeyou; Gao, Shenmao; Liu, Yuanguo; Zhang, Renfang; Dou, Guangbo (Frontiers in Psychology, 2025)
ObjectiveTo validate the reliability and validity of the Contextual Sensation-seeking Questionnaire for Skiing and Snowboarding (CSSQ-S) among Chinese adult skiers, and to explore the relationship between sensation seeking and risk-taking behavior.MethodsSnowball sampling was employed to gather data from 515 individuals, aged between 18 and 40 years old, with at least one year of experience in skiing or snowboarding. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and other statistical methods were utilized for data analysis.ResultsThe CSSQ-S demonstrated strong factor validity, internal consistency, and construct validity. Sensation seeking was significantly positively correlated with injury frequency, and risk perception mediated this relationship.ConclusionThe CSSQ-S can be regarded as a reliable and valid tool for measuring sensation-seeking levels and potential injury risks among Chinese adult skiers, providing a useful reference for ski safety management and training.